Pengkreasian Penggunaan Konjungsi Dalam Wacana Anekdot Sebagai Bahan Ajar Yang Inovatif Di Sekolah Menengah Atas - Rizkyana, Anis, Drs. Agus Budi Wahyudi, M.Hum (2017)
Conjunctions have an important role in the preparation of sentences. Conjunctions are used in connecting words with words, phrases with phrases, clauses with clauses, sentences with sentences, and paragraphs with paragraphs. Preparation of anecdotes using conjunctions. Anecdotes are used as teaching material in high school. The results of this study developed as a teaching material in accordance with KD 4.6 re-create anecdotal text by paying attention to the rules of language, both oral and written. Learning materials in high school should be developed so that students are more interested in learning. Creation of conjunction as a form of development of anecdotal teaching materials that can be done. The purpose of this research is to analyze the form of conjunction and to develop teaching materials with the creation of conjunction usage. This type of research is qualitative research. The data source in this research is a conjunction in anecdotal discourse. Data collection techniques used are referenced and noted. Researchers in analyzing the data using the method of padan and the agih method with the basic techniques divide the determinants continued orthographic and substitution technique (substitution). Based on the results of the study there are two conclusions as follows. Forms of conjunction use in the form of coordinated conjunctions, subordinate conjunctions, correlative conjunctions, and adversative conjunctions, clausal conjunctions, temporal conjunctions and the development of teaching materials in high schools.